The Effect Of Subtitution Of Potato Starch On The Pie Crust - Yossa Rezona; Wiwik Gusnita (Universitas Negeri Padang, 2021)
This research was motivated by the high production of potatoes in West Sumatra which caused the utilization of potatoes to be less than optimal. Potatoes have a high moisture content so that if they are not properly utilized, they will spoil quickly, efforts can be made to extend the shelf life of potatoes by processing potatoes into starch. Potato flour has excellent nutritional value because it contains high starch (starch) resistance so that it can be processed into pie crusts. This study aims to analyze the effect of substitution of potato starch as much as 15%, 30%, and 45% on the quality of the shape, color, aroma, texture, and taste of the pie crust. This type of pure experimental research with a completely randomized design method. The dependent variable is the quality of the pie crust using primary data sourced from 3 expert panelists by proposing an organoleptic test format. Analysis of data with ANOVA, if Fcount> Ftable then proceed with the Duncan test. The results showed that there was no significant effect of potato starch substitution on the quality of the pie crust (jagged round shape, uniform shape, neat shape, color, crunchy texture, and brittle texture) because Fcount <Ftable, and there was a significant effect of potato flour substitution. on the quality of the pie crust (aroma and taste) because Fcount> Ftable. The best results were found in X1 with 15% substitution of potato starch.